2018
DOI: 10.1002/er.4321
|View full text |Cite
|
Sign up to set email alerts
|

Determinant factors in site selection for photovoltaic projects: A systematic review

Abstract: Summary The choice of great places for installation of solar power plants has become a key issue in terms of project planning because of the increased number of investments in the photovoltaic sector. This study is a systematic review of the literature that seeks to identify the determining factors in choosing the best location for solar photovoltaic power plants, through previous research on the application of renewable energy technologies in great contexts of location. Among a total of 130 academic studies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 61 publications
0
33
0
1
Order By: Relevance
“…The main factors were classified according to point of view, such as location, economic, political, climate, and technical factors 21 . The investigation about these factors contributes to understanding the reasons why the technology has matured, consequently verifying the costs evolution and assessing the source competitiveness over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors were classified according to point of view, such as location, economic, political, climate, and technical factors 21 . The investigation about these factors contributes to understanding the reasons why the technology has matured, consequently verifying the costs evolution and assessing the source competitiveness over time.…”
Section: Resultsmentioning
confidence: 99%
“…Rediske et al 21 argue that the factors for decision‐making in the installation of renewable energy projects can be grouped into six points of view: (i) socioenvironmental; (ii) location; (iii) economic; (iv) political; (v) climate; and (vi) orography. In this research, according to the identified factors, four of these points of view were considered in the classification of the factors, besides the technical point of view was included.…”
Section: Resultsmentioning
confidence: 99%
“…When this mechanism was applied, risk at the pre-investment stage was the lowest (low risk group), and by the post-investment period it showed the highest possible value among all projects. Among the reasons for such results is the high impact of political and legislative risks [18]- [20].…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows a summary of the impact factors identified, the classification in which they were included, the references, and the total number of times they were found in the articles. In their study, Rediske et al [237] separated factors of decision making in the installation of renewable energy projects into categories. Observing the reference classifications, and adapting it for this research, according to the factors identified here, the parameters of this work were classified into five categories, based on the point of view in which they fit: (i) location factors; (ii) economic factors; (iii) political factors; (iv) climatic and environmental factors; and (v) technical factors.…”
Section: Impact Factors Identifiedmentioning
confidence: 99%